2017
DOI: 10.5585/podium.v6i2.231
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Physical Activity on Resiliency and Productivity and Reducing Staff Absence Based on Public Health of University’s Female Staff

Abstract: The purpose of this research was to study the effect of 12-week physical activity on resiliency, productivity and reducing staff absence based on public health of the female staff of Islamic Azad University. In this paper, we used the pretest-posttest quasi-experimental study designs The method of this research was semi-experimental and carried out having pre-test and post-test with pre-testpost-test design with two control and experimental groups. The population of the research was consisted of 94 individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Ten participants indicated the hike through Abel Tasman had a positive impact on resilience development, similar to the findings of Vatan et al (2017) who reported a link between physical activity and resilience. The night before the 2-day hike in Abel Tasman National Park, the students and faculty discovered the 13-mile hike was, in fact, 21 miles due to a miscalculation and unanticipated high tides.…”
Section: Student-organized Activitiessupporting
confidence: 70%
See 1 more Smart Citation
“…Ten participants indicated the hike through Abel Tasman had a positive impact on resilience development, similar to the findings of Vatan et al (2017) who reported a link between physical activity and resilience. The night before the 2-day hike in Abel Tasman National Park, the students and faculty discovered the 13-mile hike was, in fact, 21 miles due to a miscalculation and unanticipated high tides.…”
Section: Student-organized Activitiessupporting
confidence: 70%
“…Resilient leaders model positive, reflexive, and altruistic behaviors to help organizations adapt and respond to continuous change (Jackson & Daly, 2011). There are multiple approaches to help individuals build resilience which include engaging in physical activity (Haglund, Nestadt, Cooper, Southwick, & Charney, 2007;Overholt & Ewert, 2014;Vatan, Noorbakhsh, Nourbakhsh, & Nejad, 2017), practicing effective communication (Brooks & Goldstein, 2002), promoting high-involvement practices, modeling proactive behaviors, and fostering continuous learning (Kuntz, Malinen, & Näswall, 2017). Passarelli et al (2010) report that a strengths-based curriculum increases strength awareness which leads to personal growth.…”
Section: Resiliencementioning
confidence: 99%
“…According to the literature, frequent physical activity (PA) is associated with a better psychological condition, leading to a decrease in stress, anxiety, and depression [6]. Moreover, it is related to increased quality of life [7,8], productivity, satisfaction at work, capacity to make decisions, professional performance, and reduced absenteeism and related costs [9][10][11][12][13][14][15][16][17][18]. In this context, Steinhardt et al observed that sedentary POs are more absent than those who are more physically active [16].…”
Section: Introductionmentioning
confidence: 99%
“…PA is a widely studied variable, highlighting in this context some studies such as those carried out by (i) Vatan et al, who concluded that PA had a statistically significant positive impact on resilience and workers' efficiency [17]; (ii) Mohamed and Ghalab, who observed that PA had a statistically significant positive impact on professional performance [19]; and (iii) Burton et al, who showed that more active workers are more productive than inactive workers [11].…”
Section: Introductionmentioning
confidence: 99%